Dekonstruksi Identitas Michel Foucault dalam Panggung Digital Kontemporer pada Film Budi Pekerti - Umi Salamah; Rokhyanto (Universitas Insan Budi Utomo, 2026)
This study examines the phenomenon of personal identity deconstruction in cyberspace through the lens of Michel Foucault's theory of deconstruction, with the object of study being the film Budi Pekerti by Wregas Bhanuteja. In the contemporary digital landscape, identity is no longer fully controlled by the subject, but is instead reconstructed by virtual mass surveillance mechanisms. Using a descriptive qualitative method with a critical discourse analysis approach, this study dissects how the character Bu Prani experiences bodily discipline and character assassination due to the virality of a video on social media. The results show that the digital stage acts as a modern panopticon, where netizens transform into collective surveillance agents who produce a one-sided discourse of truth. Bu Prani's traditional moral authority as a teacher is deconstructed and renormalized by digital social sanctions (cancel culture). Through Wregas' visual narrative, this film represents how digital technology is not merely a medium of communication, but an apparatus of power (dispositif) that re-engineers human obedience and identity. This study concludes that in the contemporary digital stage, personal identity is fluid and fragile. It is constantly deconstructed by cyber power relations that blur the boundaries between private and public space and create modern forms of punishment that alienate subjects from their reality.